Answer :

Let f(x) = x3 – 3x2 – 13x + 15


Now, we have


x2 + 2x – 3 = 0


x2 + 3x – x – 3 = 0


(x + 3)(x – 1)


Hence, f(x) will be exactly divisible by x2 + 2x – 3 = (x + 3)(x – 1)


Now,


Using factor theorem,


If (x + 3) and (x – 1) are both the factors of f(x), then f(-3) = 0 and f(1) = 0


Now,


f(-3) = (-3)3 – 3(-3)2 – 13(-3) + 15


= - 27 – 27 + 39 + 15


= - 54 + 54


= 0


And,


f(1) = (1)3 – 3(1)2 – 13(1) + 15


= 1 – 3 - 13 + 15


= 16 - 16


= 0


Now,


Since, f(-3) = 0 and f(1) = 0


Therefore, x2 + 2x -3 divides f(x) completely.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics